A Comparative Study on the Wear Resistance of CrNiMo Cast Steels Under Dynamic Load and Ring Block Conditions - Chaoyong Li; Yi Li; Mingli Wang; Pengxiao Zhu; Cai Tang; Xu Yang; Jinyong Zhang; Yulong Qi (Metals)
Low-alloy CrNiMo cast steels are often used in the caterpillar boards of excavators in mining engineering machinery due to their good mechanical properties and low cost. Three CrNiMo cast steels with different carbon contents (0.20%, 0.29%, and 0.35% by weight) were developed in this work. The mechanical properties of ingots of these cast steels can be optimized by heat-treated quenching and tempering (QT) and surface induction hardening (QTIH). The wear behavior of QT and QTIH specimens was evaluated under dynamic load and ring block conditions. The results show that the QT specimens exhibit a good mechanical performance and wear resistance. Compared to the QT specimens, the wear resistance can be further improved by QTIH treatment. The wear weight loss of QTIH specimens decreased by 42.7% and 73.2% under dynamic load and ring block wear tests, respectively. Additionally, the strength increased while plasticity and toughness decreased with increasing carbon content. Notably, when the carbon content is 0.29%, the CrNiMo cast steel exhibits an excellent combination of strength, ductility, and wear resistance.